Scotogenic dark matter and Dirac neutrinos from unbroken gauged B − L symmetry - Julio Leite; América Morales; José W.F. Valle; Carlos A. Vaquera-Araujo (Physics Letters B, 2020)
We propose a simple extension of the standard model where neutrinos get naturally small “scotogenic” Dirac masses from an unbroken gauged B−L symmetry, ensuring dark matter stability. The associated gauge boson gets mass through the Stueckelberg mechanism. Two scenarios are identified, and the resulting phenomenology briefly sketched.